Comparative efficacy and safety of 20 intravenous pharmaceutical intervention for prevention of etomidate-induced myoclonus: a systematic review and Bayesian network meta-analysis - Chen, Lu; Zhou, Pengxiang; Li, Zhengqian; Wu, Ziyang; Zhai, Suodi (Frontiers in Pharmacology, 2025)
ObjectiveTo compare the efficacy and safety of pharmaceutical interventions to prevent etomidate-induced myoclonus (EIM), providing the optimal intervention for clinical practice.MethodsPubMed, Embase, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, Chinese National Knowledge Infrastructure, WanFang database, and SinoMed database were searched from the inception to sixth May 2024. We included randomized controlled trials (RCTs) comparing intravenous pharmaceutical interventions to prevent EIM with placebo, no intervention, or another pharmaceutical intervention.ResultsForty-eight RCTs involving 4,768 participants randomly assigned to 20 intravenous pharmaceutical interventions and normal saline were included. Granisetron (odds ratio [OR]: 0.01, 95% confidence interval [CI]: 0.00 to 0.06; one study, moderate certainty) and oxycodone (OR: 0.01, 95% CI: 0.00 to 0.05; three studies, low certainty) was found to be the most effective intervention in reducing the risk of EIM and ranked highest in terms of surface under the cumulative ranking values (94.4% and 89.7% probability), followed by sufentanil (76.5% probability) and remifentanil (74.8% probability). Further subgroup analysis of EIM at mild, moderate-to-severe levels highlighted granisetron and oxycodone as the favorable interventions for reducing EIM. For safety outcomes, the synthesized results indicated that opioids were associated with a higher risk of adverse events (AEs), while no severe AEs were observed.ConclusionModerate-to-low certainty evidence indicated that granisetron and oxycodone may represent the optimal intervention for reducing the risk of overall and moderate-to-severe EIM with a reasonable safety profile, providing the potential interventions for clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=291275.